2020
DOI: 10.5334/ijic.5456
|View full text |Cite|
|
Sign up to set email alerts
|

Communication, Collaboration and Care Coordination: The Three-Point Guide to Cancer Care Provision for Aboriginal and Torres Strait Islander Australians

Abstract: The coordination of cancer care for Indigenous Australians has been recognised as critical in addressing Indigenous patients' needs, for example in relation to navigating the health system, providing essential information and communication and ensuring cultural safety [1]. However, challenges to the provision of coordinated care to meet Indigenous cancer patients needs include: lack of communication between services; delays in receiving timely hospital information; language and cultural barriers; distance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The thematic analysis identified several concerns influencing the experiences of cancer for Aboriginal and Torres Strait Islander peoples relating to cultural insensitivity, including lack of culturally appropriate care services, language barriers, poor understanding of Aboriginal and Torres Strait Islander peoples’ perspectives about cancer and the importance of family and community involvement [ 22 , 27 , 32 , 40 , 46 , 61 64 ]. The majority of the included studies reported that care providers lacked an understanding of Aboriginal and Torres Strait Islander culture and how this shaped treatment decisions [ 42 , 46 , 65 ]. Included studies highlighted value differences between Aboriginal and Torres Strait Islander cultures and Western cultures [ 26 , 27 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thematic analysis identified several concerns influencing the experiences of cancer for Aboriginal and Torres Strait Islander peoples relating to cultural insensitivity, including lack of culturally appropriate care services, language barriers, poor understanding of Aboriginal and Torres Strait Islander peoples’ perspectives about cancer and the importance of family and community involvement [ 22 , 27 , 32 , 40 , 46 , 61 64 ]. The majority of the included studies reported that care providers lacked an understanding of Aboriginal and Torres Strait Islander culture and how this shaped treatment decisions [ 42 , 46 , 65 ]. Included studies highlighted value differences between Aboriginal and Torres Strait Islander cultures and Western cultures [ 26 , 27 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…• Some studies found that limitations in the knowledge of health professionals about cancer and the importance of cancer screening, especially in rural and remote primary healthcare settings, have affected Aboriginal and Torres Strait Islander Australians' participation in cancer screening 6,8,9,25 • Fragmented care in primary, tertiary and specialist care settings, including a lack of coordination between health professionals in these three settings, has a negative impact on the care quality, continuity of cancer care and, ultimately, the cancer outcomes for Aboriginal and Torres Strait Islander peoples 5,26,27 • Several health system factors affect Indigenous patients' acceptance of healthcare facilities and influence clients' choices and decision-making. Some of these include underrepresentation and high turnover of Aboriginal and Torres Strait Islander health professionals 28 ; health professionals dealing with multiple clinical priorities and tasks concurrently due to a shortage of facilities and staff, which affects the quality of service delivery 29 ; a shortage of female practitioners 8,20,29 ; lack of flexibility within the system 29 ; clinical staff turnover 29 ; lack of well-maintained and efficient clinical information systems for notifying, recalling and reminding women (especially sending letters) of their screening due date or appointments 29 • Health professionals' lack of education and knowledge about Indigenous cultural beliefs, rituals and needs in general is a barrier to cancer screening and care.…”
Section: Contextual Barriersmentioning
confidence: 99%
“…de Witt et al (2020) [ 1 ] was published with a typesetting error in the Results section. The original text states:…”
Section: Correctionmentioning
confidence: 99%